Therapy of Lyme borreliosis - Pauluzzi, P... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2001)
Despite many studies that have been carried out recently, there is still no standard treatment for Lyme borreliosis. The factors that must be taken into consideration in treating the disease are the intrinsic sensitivity of the pathogen Borrelia burgdorferi, tissue penetration of the antibiotic, the characteristics of the pathogen, such as long generation time (7-20 h), intracellular localization, persistence in tissues with a poor blood supply (e.g. synovia), penetration of the blood-brain barrier, and varying antibioticresistance of different pathogen strains. A generally accepted antibiotic treatment regimen has yet to be established, and all treatment recommendations are essentially provisional.
Keywords: Borrelia burgdorferi; Drug therapy; Lyme disease; Lymska bolezen sin Lymska borelioza